2018
DOI: 10.24874/ti.2018.40.02.12
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Tribological Behavior of Vinyl Ester Hybrid Composites

Abstract: An attempt has been made to explore the effect of hybrid reinforcement on mechanical properties and dry sliding wear behavior of vinyl ester (VE) composites. Vinyl ester reinforced with alkali treated coir fibers (CF-VE), silanated aramid fibers (AFs) leading to fibridization and inclusion of coconut shell powder (CSP) with various weight proportions has been prepared resulting in hybridization. Effectiveness of treated fibers and CSP on mechanical and wear behavior of VE and their hybrids was evaluated. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 44 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Qing et al [14] studied the friction and wear behaviour of short carbon fiberreinforced epoxy composites with varying nano-SiO2, and observed that 6 wt.% carbon fiber and 4 wt.% nano-SiO2 has superior wear properties. Suresha et al [15] observed that alkali treated coir fiber and silanated aramid fiber with coconut shell particles in vinyl ester influence the friction and wear behaviour of composites. Hemalata et al [16] investigated solid particle erosion wear behavior of bamboo fibre reinforced epoxy composites filled with cenosphere particles.…”
Section: Introductionmentioning
confidence: 99%
“…Qing et al [14] studied the friction and wear behaviour of short carbon fiberreinforced epoxy composites with varying nano-SiO2, and observed that 6 wt.% carbon fiber and 4 wt.% nano-SiO2 has superior wear properties. Suresha et al [15] observed that alkali treated coir fiber and silanated aramid fiber with coconut shell particles in vinyl ester influence the friction and wear behaviour of composites. Hemalata et al [16] investigated solid particle erosion wear behavior of bamboo fibre reinforced epoxy composites filled with cenosphere particles.…”
Section: Introductionmentioning
confidence: 99%
“…Alshammari et al studied the influence of woven jute fiber orientation on Tribological properties and Wear resistance of the composites and found to be better in the antiparallel orientation followed by parallel and then normal [10]. Udaya Kumar et al studied Mechanical and Tribological properties of Vinyl Ester alkali-treated coir fibers, silanated aramid fibers Composites and found that hybrid composite possess better mechanical and wear properties [11]. Some of the researchers observed the mechanical properties of woven banana polyvinyl alcohol [12] composites and found that mechanical properties improved by treatment and weaving [13].…”
Section: Introductionmentioning
confidence: 99%